PENGARUH POLA ASUH DAN KETERLIBATAN ORANG TUA DALAM PENDIDIKAN TERHADAP KEMAMPUAN SOSIAL ANAK USIA DINI DI TK NURUL FATAH KALIBARU WETAN - Friska Apsari Primadani; Nurhafit Kurniawan; Wedya Puspita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The influence of parenting patterns and parental involvement is to improve children's social skills, children's self-confidence, children's academic achievement, and develop children's emotional abilities, as well as build good relationships between children and parents. The purpose of this study was to determine the influence of parenting patterns and parental involvement in education on the social skills of early childhood in NURUL FATAH KALIBARU Kindergarten. This study used quantitative research with a survey method with samples of early childhood and parents of children in NURUL FATAH Kindergarten. Data were collected through questionnaires and observations. The research report describes in detail the results of the study, data analysis. Democratic parenting patterns and parental involvement in education have a positive influence on the social skills of early childhood in Nurul Fatah Kindergarten. Parents and educators are expected to work together to improve children's social skills through the implementation of positive parenting patterns and active involvement in education.